The seismic-historic microzoning as a fundamental complement to seismic hazard evaluation - Altez, R.; Laffaille, J. (Геодинаміка, 2008)
This paper discusses the needs to start a review process about the historical seismicity in Venezuela, from a different perspective to that used for compilation of already existent catalogues, with an interpretation intended to be more precise than exhibited by isoseismic curves assigned to most important earthquakes. У статті обговорюється необхідність початку процесу перегляду даних про історичну сейсмічність Венесуели з використанням вже існуючих сейсмічних каталогів і різних підходів з метою точнішого визначення сейсмічного ризику, ніж те, що задається ізосейстами, які належать найсильнішим землетрусам. В статье обсуждается необходимость начала процесса пересмотра данных об исторической сейсмичности Венесуэлы с использованием уже существующих сейсмических каталогов и разных подходов с целью более точного определения сейсмического риска, чем представляемое изосейстами, принадлежащими сильнейшим землетрясениям.